Rancang Bangun Sistem Informasi Pengelolaan Pembayaran SPP Berbasis Web pada SMP Fatahillah - Ibrahim Daud Syahdan; Sholihin; Elsa Safitri; Riska Rantelia Sirumapea (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
The Web-Based Tuition Fee (SPP) Payment Management Information System was designed and developed as a digital solution for financial administration at SMP Fatahillah. This internship project was conducted at the school located at Jalan Ciputat Raya No. 5, RT 04 RW 06, Pondok Pinang, Kebayoran Lama District, South Jakarta. The primary objective of this project was to develop a web-based system to support the digital management of tuition fee payments. The existing payment recording process, which relied on administrative books and physical SPP cards, caused several challenges. Recording errors, the risk of data loss, and difficulties in tracking payment information became significant issues. Delays in preparing financial reports were also unavoidable due to the manual system. The process of recording payment histories was often hindered by SPP cards that were frequently lost or not brought by students. Administrative staff also faced difficulties in verifying payment statuses when supporting documents were unavailable. The methods used in this internship project included observation, interviews, and literature studies to gather information regarding system requirements. The system development employed the Waterfall methodology, consisting of requirements analysis, system design, implementation, testing, and maintenance phases. The system was developed as a web-based application using the Laravel framework, PHP programming language, and MySQL database to support integrated, secure, and structured payment data management. The Web-Based Tuition Fee Payment Management Information System developed through this internship project provides three categories of user access rights: administrator, staff, and student. Through this system, student data management can be performed efficiently alongside the recording of every tuition fee payment transaction. Payment histories are stored systematically, and billing statuses can be displayed in real time. The system also facilitates the import of student data from Excel files. Faster and more organized payment reports are generated as the final output. A more structured and well-documented transaction recording system supports the accountability of school financial management. The system also assists administrative staff in managing payment data more efficiently, thereby improving financial information transparency. Furthermore, students can independently access the student portal to view their payment histories and billing information. The implementation of this system aims to promote effectiveness, efficiency, transparency, and accountability in tuition fee administration at SMP Fatahillah. Through this initiative, improvements in school financial governance and administrative service quality are expected to be achieved.